Intelligent Video Surveillance (IntechOpen, 2023)
The development of new technologies based on artificial intelligence and computer vision, together with the possibility of connecting different devices together in real-time, has enabled the development and progress of intelligent video surveillance. Thanks to IoT technologies, high-resolution cameras can be networked to monitor their territory, collect recordings and have them analyzed by artificial intelligence systems trained to identify critical situations. This book discusses new achievements in intelligent video surveillance solutions and their future prospects.